Peningkatan Kemampuan Berhitung dengan Menggunakan Metode Fingermathic pada Anak Usia Dini - Indaria Tri Hariani; Norma Diana Fitri (Universitas Trunojoyo Madura, 2019)
The learning process in kindergarten is still very conventional in nature. This is shown in teaching and learning activities in kindergarten Tunas Asri Benowo Surabaya, in introducing the number of teachers still using the lecture method, and memorizing. To count numbers children still write in the book given by their teacher. The research is currently doing is to improve numeracy skills in children aged 5-6 years with interesting activities for children by providing learning methods needed for children. This research method uses Classroom Action Research. The research subjects were 13 students consisting of 7 boys and 6 girls. The data analysis technique used is descriptive analysis technique. The results of this study indicate that the fingermathic method can improve numeracy skills. In the pre cycle of 69.23% which is in the criteria of Not Developing, in the first cycle the action taken through the fingermathic method increased to 53.85% in the criteria of Developing in Accordance with Expectations, and increased in the second cycle to 84.62 % on criteria according to Expectations and Very Good Developments. Based on the results of this study, it shows that an increase in numeracy skills of children aged 5-6 years with fingermathic methods